Indexes to Debate of Parliament (Hansard) - South Africa Parliament, House of Assembly (Cape Town Government Printers, 1993)
South Africa Debates of Parliament (Hansard).
South Africa Politics and government. Formed by a merger of: Debates of the House of Assembly, Debates of the House of Delegates, and Debates of the House of Representatives. 22 cm
Keywords: Indexes to Debates; Parliament; Hansard; Fifth Session - Ninth Parliament; 29 January 1993; 25 April 1994; Vol. 46; ISBN 0621156116; ISBN 0621156124; JC218429; Index to Speeches; House of Assembly; House of Delegates; House of Representatives